Introduction to Simple Accounting Technology for Traditional Market Traders in Rural Indonesia for Daily Financial Management (Pengenalan Teknologi Akuntansi Sederhana Bagi Pedagang Pasar Tradisional di Pedesaan Indonesia untuk Pengelolaan Keuangan Harian) - Fatoni, M. Anton; Ginting, Jenni Veronika Br; Kusumaningati, Iip Dyah; Elizabeth, Elizabeth; Durya, Ngurah Pandji Mertha Agung (Indonesia Berdaya, 2025)
This Community Service activity aims to improve the financial literacy of traditional market traders in rural Indonesia by introducing simple accounting technology. This program was carried out online using the Zoom platform and involved 50 participants who were market traders from several villages. The training includes material on recording daily transactions, using simple accounting applications, and preparing financial statements. Program evaluation was carried out through pre-tests and post-tests to measure the improvement of participants' understanding and questionnaires to assess satisfaction with the training. The results showed a significant improvement in the participants' skills, with the average pre-test score of 38% increasing to 80% in the post-test. In addition, 90% of the participants were satisfied with the training methods. Although online implementation is effective, internet connectivity challenges in rural areas must be considered. This program shows that a technology-based approach can be a solution to increase financial literacy among market traders. It has the potential to be implemented more widely in efforts to empower the economy of rural communities. This research is expected to be a model for similar programs.Abstrak. Kegiatan Pengabdian Masyarakat ini bertujuan untuk meningkatkan literasi keuangan pedagang pasar tradisional di pedesaan Indonesia dengan memperkenalkan teknologi akuntansi sederhana. Program ini dilaksanakan secara daring menggunakan platform Zoom dan melibatkan 50 peserta yang merupakan pedagang pasar dari beberapa desa. Pelatihan meliputi materi pencatatan transaksi harian, penggunaan aplikasi akuntansi sederhana, dan penyusunan laporan keuangan. Evaluasi program dilakukan melalui pre-test dan post-test untuk mengukur peningkatan pemahaman peserta dan kuesioner untuk menilai kepuasan terhadap pelatihan. Hasil penelitian menunjukkan peningkatan keterampilan peserta yang signifikan, dengan rata-rata nilai pre-test sebesar 38% meningkat menjadi 80% pada post-test. Selain itu, 90% peserta merasa puas dengan metode pelatihan. Meskipun pelaksanaan secara daring efektif, namun kendala konektivitas internet di pedesaan perlu diperhatikan. Program ini menunjukkan bahwa pendekatan berbasis teknologi dapat menjadi solusi untuk meningkatkan literasi keuangan di kalangan pedagang pasar. Pendekatan ini berpotensi untuk dilaksanakan secara lebih luas dalam upaya pemberdayaan ekonomi masyarakat pedesaan. Penelitian ini diharapkan dapat menjadi model bagi program serupa.